PENGETAHUAN IBU BALITA TERHADAP PEMANFAATAN BUKU KIA - Julaecha Julaecha; Ajeng Galuh W; Indarmien Netty Ariasih (Jurnal Abdimas Kesehatan (JAK), 2019)
Mother and child are groups that are vulnerable to various health problems that cause death. The mother and child health book is a tool for recording and monitoring maternal and child health, as a communication tool between health workers and families and can be used in all health facilities. Mother Toddler Classes are followed by mothers who have children between 0-5 years of age together discussing, exchanging opinions, exchanging experiences on the fulfillment of health, nutrition, and stimulation of growth and development, which are guided by facilitators using the MCH handbook. Community service aims to determine the knowledge and participation of children under five years of age on the knowledge of the use of books and participatory participation in the classes of mothers under five. The method used in community service is the lecture method used when providing information about the importance of the use and important information to monitor the growth of children listed in the MCH handbook. Results: The process of implementing a mother class of toddlers in the village of Sungai Putri, Jambi City as a whole was good, the activities related to the implementation process of Ibu Baita's classes included evaluating ownership of MCH books, exclusive breastfeeding, immunization, giving vitamin A, weighing body and stimulation of child development and the administration of MP-ASI